EVOLUÇÃO DO FENÔMENO DE ILHA DE CALOR EM CIDADE DE MÉDIO PORTE NA REGIÃO CENTRO-OESTE DO BRASIL - Paula, Diana Carolia Jesus de; Souza, Natallia Sanches e; Miranda, Soneize Auxiliadora de; Nogueira, Marta Cristina de Jesus Albuquerque; Santos, Flavia Maria de Moura (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Studies on the heat islands have proved to be an important tool for urban space management, to assist the decision making process in urban planning. However, most studies focus on large cities, but it is in medium and small cities that the root causes of the problem are facilitated by identifying the interaction between urbanization and urban climate. The objective of this article is to relate the intensity of the heat island in the urban area of Cuiabá-MT with the use and cover of the soil with maximum allowed occupation. The methodology used is the mobile night transect, passing through 19 points of the city. The results indicated that the highest percentage of impermeable coverage is those in which the occupation allowed varies between 60 and 80% of the area. It is also observed that in both transects in 70% of the points the intensity of the island is strong, varying between 4.1 and 5.3 ° C. Therefore, this article corroborates with heat island studies in a medium-sized city with a tropical climate in the Midwest region, considering that few studies focus on the investigation of the urban climate in the region.